SYNTHESIS AND BIOLOGICAL ACTIVITY OF SOME BARBITURIC ACID DERIVATIVES VIA SCHIFF΄ S BASES - Hello, Kasim; Shneine, Jawad; Numan, Ahmed (Iraqi Journal of Science, 2024)
The present work includes the synthesis of different Schiff bases by the reaction of aniline with benzaldehyde and its derivatives. These Schiff bases reacted with phenoxy acid chloride to yield acetanilide derivatives. The synthesis of barbituric acid derivatives has been performed by the reaction of phenoxyacetanilide derivatives with guanidine carbonate and diethyl malonate (DEM) derivatives. Elemental analysis and FT-IR spectroscopy were used to characterize the prepared compounds.The antibacterial activity of the products were studied in vitro using disc diffusion method against two pathogenic strains of bacteria (Pseudomonas aeuroginosa and Staphylococcus aureus) and showed high activity against both types.